Developmental alterations of indirect-pathway medium spiny neurons in mouse models of Huntington's disease - Margaux Lebouc; Léa Bonamy; Thibault Dhellemmes; Jakob Scharnholz; Quentin Richard; Gilles Courtand; Alexandre Brochard; Frédéric Martins; Marc Landry; Jérôme Baufreton; Maurice Garret (Neurobiology of Disease)
Huntington's disease (HD) is a complex neurodegenerative disorder with cognitive and motor symptoms that typically manifest in adulthood. However, embryonic brain development impairments leading to cortical defects in HD mutation carriers has been shown recently supporting a neurodevelopmental component in HD. Despite HD is primarily recognized as a striatal pathology, developmental alterations in this structure, particularly during the early postnatal period, remain poorly understood. To fill this gap, we examined striatal development in newborn R6/1 mice. We found that D2 receptor-expressing indirect-pathway medium spiny neurons (D2-MSNs) present in the matrix striatal compartment undergo early morphological and electrophysiological maturation. Altered electrophysiological properties were also observed in newborn CAG140 mice. Additionally, we also observed a D2-MSN-selective reduction in glutamatergic cortico-striatal transmission at the beginning of the second postnatal week as well as a reduced projection of D2-MSNs onto the GPe at birth in R6/1 mice. All these alterations were transient with the circuit normalizing after the second postnatal week. These results identify a compartment- and cell-type specific defect in D2-MSNs maturation, which can contribute in their latter vulnerability, as this cell-type is the first to degenerate in HD during adulthood.